The Turkish Cypriot Legal System From a Historical Perspective - Turhan, Turgut (Ankara Bar Review, 2010)
[Abstract Not Available]
This article was originally written in Turkish and translated by Kadir Yılmaz, Cansu Akgün, Ece Yılmaz, Cihangir Karabıyık, Levent Aydaş, Altan Liman and Nursel Atar.
Keywords: Legal System - Law - History - Turkish Cyprus (North); Legal System - Law - Turkish Cypriots